Musik Populer dalam Dakwah Islam di Indonesia - Marufah, Hafidhoh (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
In the late 1990s, popular music with Islamic values ​​emerged in Indonesia’s music and recording industry. This music features lyrics containing Sufism values. The musicians are also spiritual leaders for the audience. Knauth found three main genres representing popular Islamic music in Indonesia from 2002-2007 through an ethnographic approach. The three genres are nasyid with musicians Aa Gym, Islamic rock with musicians Ahmad Dhani and Dewa 19, and Islamic fusion with Cak Nun and Kiai Kanjeng. Benedict Anderson's theory of Javanese power and leadership and the theory of Islamic political scholar John Esposito compare these leaders (musicians). Knauth explained how the spiritual journey of the three influenced the songs they performed. The lyrics of the song contain various monotheism and tasawuf teachings.